The Analysis of Foreign Bank Presence Factor on the Factor of Economic growth Indonesia using Confirmatory Factor Analysis (CFA) - Siti Epa Hardiyanti; Yayan Haryanto (PT Larva Wijaya Penerbit, 2022)
Indonesia is an emerging country which will be develop to industrial country. This paper examines the main implications about foreign bank presence on the Indonesia’s economy. We find that the Foreign Bank Presence has negative effect on Indonesia’s Economy. The determinant factor of foreign bank presence is Foreign Number and Capital Adequacy Ratio (CAR) can be used to confirm determinant factors of Foreign Bank Presence but Foreign Shares cannot be used to confirm determinant factors of Foreign Bank Presence. While, Gross Domestic Product (GDP) and Inflation Rate can be used to confirm determinant factors of Indonesia’s Economy. But direct effect of foreign number on Gross Domestic Product (GDP) is positive effect, and direct effect of capital adequacy ratio on inflation rate is negative effect.